The level of sport activity of students from three institutions of higher education - Fučkar Reichel, K. (Array, 2008)
The purpose of this study was to establish difference in the level of sport activity of students before and after enrolment to the Faculty, and their attitude to participate in their teams. The research was conducted on a sample of 1358 students (encompassing both male and female gender) from three Zagreb’ s institutions of higher education with majors in humanities and social sciences, and natural sciences and engineering. The results show that about one forth of students never participated in any type of sport activity before the Faculty. On the other hand those who have, where either active in team sports (typically male students) or in sport-recreational activities (typically female students). After enrolment to the Faculty this level of sport activity changes signifi cantly. With less than 10 % of initially inactive male students, this number grew up to 41, 53%, meanwhile in female students this percentage grew from 15, 52 % up to 66, 45%. The difference among female students is not the refl ection of institution they attend or their major, however this is not the case with male students. Participation in recreational sports in three examined institutions of higher education is essentially the same, but differences are noticeable by gender in favor of male students. The percentage of both female and male students that want to compete in team sports and participate in sports union of higher education differs by gender in favor of male students, with no relevant differences among different institutions of higher education.